The Effect Of Laser Power And Scanning Speed On The Density Of Selective Laser Melting Fabricated AL-CNT Composites - Du, Zhenglin (2016)
AlSi10Mg reinforced with carbon nanotubes were fabricated using selective laser melting manufacturing process. The influence of laser power and scanning speed on the densification behavior and microhardness were studied. Near fully dense nanocomposite parts with 97% theoretical density were achieved with increasing energy density. Microhardness was observed to slightly decrease as energy density increases. This could be attributed to the increase in grain size as energy density increases.